Analysis Issues on Seismic Assessment of Existing Structures - Sousa, Romain (2020)
Many existing RC structures worldwide were designed for gravity loads only, with inadequate lateral load resistance, lateral stiffness and poor detailing of the reinforcement. Moreover, the concept of regularity both in plan and elevation that characterise a good conceptual design was, in most cases, not taken into account. The introduction in Europe of the regulations for seismic assessment of existing structures imposed stricter performance requirements for building structures. In order to take into account the poor seismic behaviour of such buildings, recent seismic codes – namely EC8 and NTC08, introduce a number of prescriptions regarding issues such as analysis type, load distribution, accidental eccentricity, etc. At the same time, these codes give room for engineering judgment to be used with reference to the definition of structural and non-structural elements such as slabs or infill walls, and obviously leave it up to the analyst decisions regarding Finite Elements typology, meshing, mass modelling, etc. The main goal of this work is thus to provide an extensive and wide evaluation on the influence of each of the abovementioned parameter on the seismic assessment of structures. For this purpose, nonlinear static analysis, as well as nonlinear dynamic analysis are performed on a real building that has also been experimentally tested in the past. The results will hopefully provide indications on the relative importance of each modelling parameter or decision.